2011
DOI: 10.1248/bpb.34.415
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Gastrointestinal Absorption of Ovalbumin Caused by Spermine Induces an Increase in Plasma Histamine Levels in Mice Sensitized to Ovalbumin

Abstract: The polyamines spermidine and spermine (SPM) and their precursor putrescine are ubiquitous polycationic compounds found in all mammalian cells. [1][2][3][4][5] These compounds are essential for the maintenance of cell growth in many tissues, and intracellular levels of polyamines are maintained within narrow limits.The polyamines are present in variable amounts in almost all food or foodstuffs. In humans, a typical diet might contribute hundreds of micromoles of polyamines per day to the gut lumen, 6,7) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Thus, the mechanisms for enhanced OVA absorption may be different between aspirin and spermine. However, Sugita et al also showed that coadministration of OVA and spermine increased in plasma histamine levels, as well as OVA absorption, in mice sensitized with OVA compared with oral administration of OVA alone [20]. Thus, we consider that both spermine and aspirin could enhance the oral absorption of OVA as an intact form at least partly.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the mechanisms for enhanced OVA absorption may be different between aspirin and spermine. However, Sugita et al also showed that coadministration of OVA and spermine increased in plasma histamine levels, as well as OVA absorption, in mice sensitized with OVA compared with oral administration of OVA alone [20]. Thus, we consider that both spermine and aspirin could enhance the oral absorption of OVA as an intact form at least partly.…”
Section: Discussionmentioning
confidence: 92%
“…4). Moreover, Sugita et al 34) showed that oral ingestion of spermine increased OVA absorption by modulating the paracellular pathway. These results strongly indicate that ASP facilitates the paracellular pathway and allergen absorption, and that augmentation is not affected by allergen properties such as molecular size and electric charge.…”
Section: Discussionmentioning
confidence: 99%